DOVE' S REAL BEAUTY: HEALTH CONCERN OR ADVERTISING STRATEGY? (Fiep Bulletin - online, 2015)
Many are the themes approached and the attitudes suggested by advertisement campaigns, but those directed to the female population bring about some singular aspects, especially regarding behavior, taste, nimbleness, ideals, the female appearance. In various moments, the woman may feel as if oriented by a manual of social behavior, a role now played by advertising. And, in this search, the woman wants to assimilate standards that are familiar, that are part of the culture she is inserted to. The campaign analyzed in this article, entitled Dove's Real Beauty, proposes a rearrangement of the female imaginary or, simply, points to another consuming strategy? That is the problem this article tries to solve.
Keywords: female body; advertising; Aesthetics.